Factors Associated with Body Mass Index among Adolescents of Changunarayan Municipality, Bhaktapur - Gurung, Neera; Devkota, Pooja; Devkota, Pragya; Shrestha, Archana (Journal of Advanced Academic Research, 2025)
Body Mass Index (BMI) is widely used, straightforward measure that relates weight to height and is commonly applied to assess nutritional status. Individuals with a BMI of 25 or higher are classified as overweight. A person with a BMI equal to or more than 25 is considered as overweight. Overweight and obesity are the major factors of many non-communicable diseases. Nutritional status refers to an individual’s health condition as influenced by the intake and effective utilization of nutrients. Obesity is characterized by excessive or abnormal fat accumulation that poses health risks. Adolescence is a crucial period during which the risk of developing overweight and obesity significantly increases. Overweight and obesity are the major development of overweight and obesity. This study aimed to assess the prevalence of nutritional status and identify factors associated with overweight among school-going adolescents in selected schools within Changunarayan Municipality. A school based cross-sectional study was carried out among 250 students aged 10-19 years from grades 8,9 and 10 in private schools of Changunarayan Municipality, Bhaktapur. The findings revealed that 50.8% of the students had a normal weight, 43.2% were underweight, while overweight and obesity were observed in 4% and 2% of the participants, respectively.